Case Reports: Painful Limbs/Moving Extremities: Report of Two Cases - Miyakawa, Tsuyoshi (Springer-Verlag, 2010)
BACKGROUND: Painful limbs/moving extremities is a relatively rare condition characterized by aching pain in one limb and involuntary movement in the affected fingers or toes. Its pathomechanism is unknown. We report two patients with painful limbs/moving extremities. In one patient with a painful arm and moving fingers, the symptoms were resolved after surgery. CASE DESCRIPTIONS: Patient 1 was a 36-year-old man with a painful arm and moving fingers. Treatment with administration of analgesics was not effective. Postmyelographic CT showed stenosis of the right C5/C6 foramen attributable to cervical spondylosis and a defect of the contrast material at the foramen. He was treated with cervical foraminotomy. Patient 2 was a 26-year-old woman with a painful leg and moving toes. The pain and involuntary movement appeared 2 weeks after discectomy at L5/S1. Lumbar MRI and myelography showed no indications of nerve root compression. She was treated with a lumbar nerve root block. The pain and involuntary movement completely disappeared in both patients after treatment. LITERATURE REVIEW: Numerous studies report treatments for painful limbs/moving extremities, but few report successful treatment. Recently, botulinum toxin A injection and epidural spinal cord stimulation have been used and are thought to benefit this condition. Successful surgical treatment previously was reported for only one patient. PURPOSES AND CLINICAL RELEVANCE: If imaging indicates compression of nerve tissue, we believe surgical decompression should be considered for patients with painful limbs/moving extremities who do not respond to nonoperative treatment. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s11999-010-1437-y) contains supplementary material, which is available to authorized users.